2018
DOI: 10.1037/pspp0000152
|View full text |Cite
|
Sign up to set email alerts
|

Perceived problem-solving deficits and suicidal ideation: Evidence for the explanatory roles of thwarted belongingness and perceived burdensomeness in five samples.

Abstract: Perceived social problem-solving deficits are associated with suicide risk; however, little research has examined the mechanisms underlying this relationship. The interpersonal theory of suicide proposes 2 mechanisms in the pathogenesis of suicidal desire: intractable feelings of thwarted belongingness (TB) and perceived burdensomeness (PB). This study tested whether TB and PB serve as explanatory links in the relationship between perceived social problem-solving (SPS) deficits and suicidal thoughts and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 116 publications
(175 reference statements)
5
37
1
3
Order By: Relevance
“…It could be that perceived burdensomeness is more affiliated with suicidal ideation and that constructs like feeling disconnected and hopelessness have a stronger correlation to suicidal desire (Klonsky & May, ). These are preliminary results that add to emerging research indicating that suicidal desire and suicidal ideation are separate constructs impacting suicide risk (Chu et al, ; Klonsky & Dhingra, ).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…It could be that perceived burdensomeness is more affiliated with suicidal ideation and that constructs like feeling disconnected and hopelessness have a stronger correlation to suicidal desire (Klonsky & May, ). These are preliminary results that add to emerging research indicating that suicidal desire and suicidal ideation are separate constructs impacting suicide risk (Chu et al, ; Klonsky & Dhingra, ).…”
Section: Discussionsupporting
confidence: 64%
“…Considering recent work indicating that suicidal ideation and suicidal desire variables are distinct (Klonsky & Dhingra, ) and that thwarted belongingness and perceived burdensomeness can provide unique pathways to suicidal ideation (Chu et al, ), we further analyzed our proposed model with suicidal ideation as the outcome variable. Suicidal ideation was positively skewed and leptokurtic (suicidal ideation ranged from 0 to 17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous researchers have found that con dence in solving problems is a protective factor for depression [41]. Lack of con dence and defects in problem solving are related to the risk of suicide [42,43]. The ability to solve problems rationally can reduce the negative effects of physical abuse on women's suicidal ideation [44].…”
Section: Discussionmentioning
confidence: 99%